Prenatal exposure to fine particulate matter and the risk of spontaneous preterm birth: A population-based cohort study of twins - Qiao, Ping; Fan, Kechen; Bao, Yirong; Yuan, Ling; Kan, Haidong; Zhao, Yan; Cai, Jing; Ying, Hao (Frontiers in Public Health, 2022)
Studies in singletons have suggested that prenatal exposure to fine particulate matter (PM2.5) and some of its chemical components is associated with an increased risk of preterm birth (PTB). However, no study has been conducted in twins. In a twin birth cohort of 1515 twin pairs and their mothers, we examined the associations of maternal exposure to PM2.5 total mass and its carbonaceous components with PTB in twins. Participants who had iatrogenic PTBs were excluded. Maternal exposure to total PM2.5 mass and two carbonaceous components, namely, organic carbon (OC) and black carbon (BC), was estimated by a satellite-based model. The associations between PM2.5 exposure and the risk of spontaneous PTB were evaluated by logistic regression analysis. This study found that exposure to total PM2.5 mass and OC during the second trimester of pregnancy was significantly associated with an increased risk of spontaneous PTB. An interquartile range (IQR) increase in total PM2.5 mass and OC exposure during the second trimester was associated with 48% (OR=1.48, 95% CI, 1.06, 2.05) and 50% (OR=1.50, 95% CI, 1.00, 2.25) increases in the odds of PTB, respectively. However, no significant association was found between BC exposure during any exposure window and the risk of PTB. The findings suggest that exposure to ambient air pollution with fine particles may be a risk factor for spontaneous PTB in twin pregnancies. The middle stage of pregnancy seems to be a critical window for the impacts of PM2.5 exposure on PTB in twin pregnancies.